Theoretical density functional study of substituted dioxanes: trans 3,6-dimethoxy-1,2-dioxane - Castro, Eduardo Alberto (2003)
A theoretical Density Functional study of the trans-3,6-dimethoxy-1,2-dioxane molecule is performed with the purpose to analyze different conformational features.The energetic stability of the different isomers is discussed in terms of several electronic factors. Results are compared with previous semiempirical studies and they are discussed in a comparative fashion. Final results show that ab initio studies allow one to overcome some drawbacks derived from the semiempirical techniques.